2016
DOI: 10.1007/s11010-016-2780-4
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia reduces integrin subunits alpha v and alpha 5 on the surface of dermal fibroblasts contributing to deficient migration

Abstract: Deficient wound healing is a common multifactorial complication in diabetic patients, but the cellular and molecular mechanisms involved are poorly defined. In the present study, we analyzed the effects of hyperglycemia on integrins expression in rat dermal fibroblasts and addressed its role in cell adhesion and migration. Diabetes Mellitus was induced in rats by streptozotocin injection and maintained for 30 days. Primary cultures of dermal fibroblasts from control and diabetic rats were maintained under low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 28 publications
3
21
0
2
Order By: Relevance
“…Moreover, integrin expression levels are sensitive to glucose level in different cell types. Hyperglycaemia may thus modify integrin expression and its intracellular signalling in β‐cell, comparable to that observed in endothelial cells (Roth et al., ) or fibroblast (Almeida et al., ).…”
Section: Ecm Adhesion and Diabetessupporting
confidence: 56%
“…Moreover, integrin expression levels are sensitive to glucose level in different cell types. Hyperglycaemia may thus modify integrin expression and its intracellular signalling in β‐cell, comparable to that observed in endothelial cells (Roth et al., ) or fibroblast (Almeida et al., ).…”
Section: Ecm Adhesion and Diabetessupporting
confidence: 56%
“…Indeed, Varner et al [19] reported that cell behavior depends on the adhesion to FN and on ITGA5 subunit expression. Moreover, a recent study showed that the migration ability of dermal fibroblasts improved following their exposure to FN [27]. …”
Section: Discussionmentioning
confidence: 99%
“…The selection of the pore size was based on previous literature studies which used this type of transwell system to evaluate fibroblast migration [14, 15]. It was also considered the characteristics of the fibroblast cell type, such as their size (10–15 um).…”
Section: Methodsmentioning
confidence: 99%